Regulatory role of TIGAR on endothelial metabolism and angiogenesis. Issue 11 (30th April 2021) - He, Xiaochen; Zeng, Heng; Cantrell, Aubrey C.; Chen, Jian‐Xiong
Abstract: Endothelial glycolytic metabolism plays an important role in the process of angiogenesis. TP53‐induced glycolysis and apoptosis regulator (TIGAR) is a significant mediator of cellular energy homeostasis. However, the role of TIGAR in endothelial metabolism, angiogenesis, and coronary flow reserve (CFR) has not been studied. The present study investigated whether knockout (KO) of TIGAR improves endothelial glycolytic function and angiogenesis. In vitro, aortic endothelial cells (ECs) from TIGAR KO mice exhibited increased expression of 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐bisphosphatase isoform‐3 (PFKFB3) and increased glycolytic function. These were accompanied by increased mitochondrial basal/maximal respiration and ATP production. Furthermore, knockout of TIGAR in ECs enhanced endothelial proliferation, migration, and tube formation. Knockout of TIGAR also significantly increased aortic sprouting ex vivo. In vivo, knockout of TIGAR increased the expression of proangiogenic factor, angiopoietin‐1 (Ang‐1) in mouse hearts. Knockout of TIGAR also significantly increased coronary capillary density with enhanced CFR in these hearts. Furthermore, TIGAR KO mice subjected to pressure overload (PO), a common model to study angiogenesis and cardiac hypertrophy, exhibited elevated expression of Ang‐1, VEGF, and PFKFB3 than that of the wild‐type (WT) mice. WT mice subjected to PO exhibited a significant reduction of coronary capillary density and impaired CFR, but TIGAR KO mice did not. In addition, knockout of TIGAR blunted TAC‐induced cardiac hypertrophy and dysfunction seen in the WT mice. In conclusion, knockout of TIGAR improves endothelial angiogenetic capabilities by enhancing the endothelial glycolytic function, mitochondrial respiration, and proangiogenic signaling, which leads to increased coronary capillary density and vascular function and protects against chronic stress. Abstract : The first study showing that ablation of TP53‐induced glycolysis and apoptosis regulator (TIGAR) improves endothelial glycolytic function, mitochondrial respiration, and angiogenic capacity in vitro. Knockout of TIGAR promotes proangiogenic signaling, by increasing the expression of Ang‐1, VEGF, and PFKFB3, and enhances myocardial angiogenesis and coronary flow reserve under pressure overload. Knockout of TIGAR preserves cardiac function by rebalancing angiogenesis with cardiac hypertrophy under stress.